MAKNA MEDIASI DALAM UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Sudjana, Sudjana (Veritas et Justitia, 2021)
Art. 95(4) Law No. 28 of 2014 re. Copyright determines that mediation should be the preferred choice to settle copyright disputes, including those that relates to piracy and plagiarism. The issue to be discussed here is what would the legal consequence be in case this alternative dispute settlement is not utilized by disputants. This problem will be discussed using a juridical normative approach. Here, mediation is understood in the context of Law No. 30 of 1999 re.  Arbitration and Alternative Dispute Settlement and Supreme Court Regulation No. 1 of 2016 re. Mediation Procedure in Court Proceedings. The main finding of this legal research is that mediation, by law, should be offered in court or may be used out of court at any time by disputants, in civil dispute (claim for compensation) as well in criminal cases.  Non utilisation does not have as consequence the cessation of existing court proceedings.